Analysis of Mexican young women with primary ovarian insufficiency induced by gynaecological and haematological cancer management - Marisol García-García; David Cantú-; Rosa Salcedo-Hernández; Aarón González-Enciso; Cintia María Sepúlveda-Rivera; Julio César González Rodríguez; Salim Abraham Barquet-Muñoz (Taylor & Francis Group, 2023)
This was a retrospective study that included 114 women younger than 40 years with induced primary ovarian insufficiency. Patients who presented vasomotor symptoms had a higher proportion (26 [63.41%] versus 58 [79.45%], OR 2.23, 95% CI 0.95-5.23, p = .065) to initiate hormone replacement therapy. Vasomotor symptoms were present in patients with ovarian cancer (OR 0.27, 95% CI 0.09-0.8, p = .18), haematologic cancer (OR 0.11, 95% CI 0.2-0.65, p = .014), radiotherapy (OR 2.62, 95% CI 1.04-6.54, p = .039) and chemotherapy with radiotherapy (OR 2.72, 95% CI 1.01-7.35, p = .049). Having ovarian or haematological cancer, being managed with radiotherapy and/or chemotherapy, and having follicle-stimulating hormone parameters higher than 35 mUI/mL are factors that significantly increase the risk of presenting vasomotor symptoms.Impact Statement What is already known on this subject? In young women with cancer, induced primary ovarian insufficiency can result as an ovarian surgery or as an adverse effect of chemotherapy or radiotherapy. Regardless of aetiology, patients are going to manifest early climacteric symptoms with an increased risk for cardiovascular disease, metabolic syndrome and osteoporosis. What do the results of this study add? Patients who presented vasomotor symptoms had initially a higher proportion of hormone replacement therapy. Patients that were treated exclusively with radiotherapy or with chemotherapy and concomitant radiotherapy have a significantly increased risk to manifest vasomotor symptoms. What are the implications of these findings for clinical practice and/or future research? Having ovarian or haematological cancer, being managed with radiotherapy and/or chemotherapy and having follicle-stimulating hormone parameters higher than 35 mUI/mL are factors that significantly increase the risk of presenting vasomotor symptoms.